Ifo World Economic Survey August 2003 - Gernot Nerb; Anna Stangl (Ifo World Economic Survey, 2003)
World Economic Climate: World Economic Climate brightens; Economic Expectations: Economic expectations for the next six months improved, but current economic situation remains unsatisfactory; Inflation: Inflation expected to slow down; Interest Rates: Renewed decline of interest rates expected; Currencies: Euro seen as overvalued; Special Topic: SARS epidemic had temporary negative impact on economic sentiment worldwide
Keywords: 330